Community voices on climate, peace and security: Guatemala - Medina, Leonardo; Madurga Lopez, Ignacio M.; Penel, Charlotte; Higuera-Florez, Julian; Pacillo, Grazia; Läderach, Peter R.D.; Hellin, Jon; Sieber, Stefan; Bonatti, Michelle (2023)
This study conducted a participatory appraisal of climate vulnerabilities and conflict risks three communities across Guatemala: 1) Maya Chʼortiʼ Indigenous Peoples farmers in La Lima village, Camotán, Chiquimula department; 2) Farmers, ranchers and sand harvesters in Tenedores village, Morales, Izabal department; and 3) Farmers in El Carpintero village, Chiantla, Huehuetenango department. The impacts of climate variability in Guatemala are leading to the depletion of natural resources and the destabilization of established weather patterns, which are critical for many livelihoods. These climate-related extremes are intensifying the vulnerability of local communities and amplifying existing challenges to societal stability and conflict. This includes issues such as a lack of political legitimacy, exclusive control over natural resources, the presence of illicit sources of income, criminal violence, a large informal economy, insecure land and resource rights, and widespread inequality and marginalization. In addition to these preexisting drivers of instability, the effects of climate change are compounding the situation and exacerbating trends in irregular migration. This poses additional security risks for those on the move. Moreover, these sources of instability and conflict are eroding the capacity of local populations to adapt to climate change and work together to build resilience. Six climate security pathways, as experienced by local populations, are identified and discussed within the report. Conflict-sensitive resilience building action urgently needs to be deployed in accordance with community-level priorities, in a way that builds upon local and Indigenous knowledge, everyday experience of problem dynamics, and perceptions around structural sources of vulnerability and conflict. Community members developed context-specific policy recommendations to turn climate-related security risks into opportunities for resilience and peacebuilding. These recommendations are discussed in detail.